(untitled) (Fiep Bulletin - online, 2015)
Despite the importance of power production in human movement analyses, this is one of the least examined biomechanical parameter. This fact can be attributed to the difficulty in measuring this parameter and its abstract nature (Enoka, 2000). The present paper examines power values of several people performing Kung Fu strikes. For that, seven individuals were requested to hit a high-density rubber surface, performing Yau-Man Kung Fu “palm” strikes. A high-speed camera at a 1000 fps rate recorded all strikes. The results show power values up to 1200 W and that Kung Fu adept practitioners obtained larger values compared to the control group. The paper also concludes that after a few years of training, individuality is the most determinant factor in the power magnitude of one’s strikes.